Kanski's clinical ophthalmology : a systematic approach - Salmon, John F.; Kanski, Jack J. ([Amsterdam] : Elsevier, 2025)
"Filled with stunning images and in-depth information on both common and rare ophthalmic diseases and disorders, Kanski's Clinical Ophthalmology: A Systematic Approach, 10th Edition, is both a foundational knowledge source for trainees and a valuable reference for experienced practitioners. Dr. John Salmon, from the University of Oxford, has meticulously revised this classic text, retaining Dr. Kanski's highly effective format of succinct text and visually dynamic presentation. Extremely well organized and comprehensive in scope, it provides authoritative, focused guidance on diagnosis and management, facilitating quick comprehension to enhance learning, aid exam preparation, and guide clinical practice" --
Examination Techniques -- Eyelids -- Lacrimal Drainage System -- Orbit -- Dry Eye -- Conjunctiva -- Cornea -- Corneal and Refractive Surgery -- Episclera and Sclera -- Lens -- Glaucoma -- Uveitis -- Retinal Vascular Disease -- Acquired Macular Disorders -- Inherited retinal degenerations -- Retinal Detachment -- Vitreous Opacities -- Strabismus -- Neuro-ophthalmology -- Ocular Tumours -- Ophthalmic Side Effects of Systemic Medication -- Trauma
Includes index
Keywords: Ophthalmology(DNLM)D009885; Eye Diseases(DNLM)D005128; Diagnostic Techniques, Ophthalmological(DNLM)D003941; Ophthalmologic Surgical Procedures(DNLM)D013508